Penerapan PJBL sebagai Langkah Mempersiapkan Kreativitas Siswa SD untuk Menghadapi Era 5.0 - Dharmesthi Anindyajati; Sholihah Mar'atus; Suwardi Dheliana; Nur Ngazizah (Indonesian Publication Center, 2023)
Education is a place for someone to dig up information through the knowledge learned in schools or educational units. Schools are also a place for students to develop their talents and abilities. One of the skills that can be honed at school is the ability to be creative. Creativity or creativity is one of the highest levels of thinking. Creative attitude is the thinking ability of students to create something. One way that educators can do is to develop learning models that can improve creative thinking skills. The Project Base Learning learning model is one of the breakthroughs that can be used by educators and schools to increase the creativity of their students in addition to the lack of facilities and infrastructure and the limited ability of teachers at SD N Sokowaten. This learning model can also be used as a forum for schools to help students prepare for the era of technological development and the 5.0 era.